The Role of Hydration and N-Acetyl Cysteine Combination in 48Hours Contrast-Induced Nephropaty after Percutaneous CoronaryIntervention in Stage Three Chronic Kidney Disease Patients - Simatupang, Lydia D; Susalit, Endang; Wijaya, Ika Prasetya (Jurnal Penyakit Dalam Indonesia, 2016)
Introduction. Contrast Induced Nephropathy (CIN) after percutaneous coronary intervention (PCI) is common in stage 3 chronic kidney disease (CKD) patients. While there is no cure for CIN and some cases are fatal for the kidney or even life, it is preventable. Eventhough controversial, hydration and N-Acetyl Cysteine (NAC) are modalities to prevent CIN. Not having a certain guideline to prevent CIN in Integrated Cardiac Services (ICS) Cipto Mangunkusumo Hospital for PCI patients generates interest to study it. Methods. A prospective cohort is conducted to evaluate plasma creatinine before and 48 hours after PCI, meanwhile recording whom is given combined hydration and NAC and which not. Results. 43,4% of stage 3 CKD patients are given hydration and NAC, and incidence of CIN occurred in 5.26% patients all belonging to the non hydration and NAC group. Attributable risk is 100% means CIN can be prevented with hydration and NAC. Conclusions. Hydation and NAC is indicated to be protective against CIN in stage 3 CKD patients undergoing PCI.